3D Mesh Deformation Technology for Generation of Virtual Garments (Journal of Fiber Bioengineering and Informatics, 2018)
In recent years, the area of sketch-based virtual garments generation has attracted more and moreattention. In this paper, we propose a new method to develop 3D virtual garments by applying meshdeformation technology for the sketch-based approach. Compared to the traditional methods, the 3Dgarments, generated by our method, can be obtained easily and directly. The technology of meshdeformation in our paper involves two algorithms: Laplacian mesh editing/optimization, and mean-valuegeometry encoding/decoding. Given the modified positions for a set of anchor vertices, the mean-valueencoding and decoding are used to transform the positions for the rest of the mesh vertices. Laplacianmesh editing and optimization are capable of improving the quality of the triangulation while preservingthe shape properties of the original models. The resulting 3D garment validates the effectiveness of theproposed method.